Body Image Ditinjau dari Jenis Kelamin pada Masa Dewasa Awal - Omega Lambulalo Rengga; Christiana Hari Soetjiningsih (Faculty of Psychology, Universitas Semarang, 2022)
Abstract. Body image consists of self-perception, emotional cognition, and behavior related to one's physical appearance. Evaluating how individuals react to changes in body shape, capacity, and function is very important for men and women in early adulthood. The evaluation results can produce a positive body image or a negative body image. The purpose of the study was to examine the differences in body image between men and women in early adulthood. The participants consisted of 54 men and 54 women. The research instrument used was the Multidimensional Boddy Self-Relation Questionnaire Appearance Scale (MBRSQ-AS). Data analysis used an independent sample T-test. The results of the comparison test show that there is no difference in body image between men and women in early adulthood. Keywords: Body Image, Gender, Early AdulthoodAbstrak. Body image terdiri dari persepsi diri, kognisi emosi, dan perilaku yang terkait dengan penampilan fisik seseorang. Mengevaluasi bagaimana individu bereaksi terhadap perubahan bentuk tubuh, penampilan dan fungsi sangat penting untuk laki-laki dan perempuan masa dewasa awal. Hasil evaluasi dapat menghasilkan body image positif ataupun body image negatif. Tujuan penelitian menguji perbedaan body image antara laki-laki dan perempan pada masa dewasa awal. Partisipan terdiri dari 54 laki-laki dan 54 perempuan. Instrumen penelitian menggunakan skala Multidimensional Boddy Self-Relation Questionnaire Apperance Scale (MBRSQ-AS). Analisis data menggunakan Uji Independent Sample T-test. Hasil uji komparasi menunjukan tidak ada perbedaan body image antara laki-laki dan perempuan pada masa dewasa awal. Kata kunci: Body Image, Jenis Kelamin, Masa Dewasa Awal